On Teaching Discrete Mathematics to Freshman Computer Science Students - Faron Moller (Journal of Higher Education Theory and Practice, 2019)
Discrete Mathematics is an inevitable part of any undergraduate computer science degree programme. However, today's computer science student typically finds this to be at best a necessary evil with which they struggle to engage. Twenty years ago, we started to address this issue seriously in our university, and we have instituted a number of innovations throughout the years which have had a positive effect on engagement and, thus, attainment. In this paper, we describe and motivate the innovations which we introduced, and provide a detailed analysis of how and why engagement and attainment levels varied over two decades as a direct result of these innovations